A literature review of the impact of exclusion criteria on generalizability of clinical trial findings to patients with chronic pain. (11th November 2022) - Salmasi, Vafi; Lii, Theresa R.; Humphreys, Keith; Reddy, Vinay; Mackey, Sean C.
Abstract : Patients with chronic pain are frequently excluded from trials because of comorbidities. More inclusive studies will have better generalizability considering differences between excluded and included patients. Abstract: The ability of clinical trials to inform the care of chronic pain may be limited if only an unrepresentative subset of patients are allowed to enroll. We summarize and report new insights on published studies that report on how trial exclusions affect the generalizability of their results. We conducted a PubMed search on the following terms: (("eligibility criteria" AND generalizability) OR ("exclusion criteria" AND generalizability) OR "exclusion criteria"[ti] OR "eligibility criteria"[ti]) AND pain. We only considered studies relevant if they analyzed data on (1) the prevalence and nature of exclusion criteria or (2) the impact of exclusion criteria on sample representativeness or study results. The 4 articles that were identified reported differences in patients who were included and excluded in different clinical trials: excluded patients were older, less likely to have a paid job, had more functional limitations at baseline, and used strong opioids more often. The clinical significance of these differences remains unclear. The pain medicine literature has very few published studies on the prevalence and impact of exclusion criteria, and the outcomes of excluded patients are rarely tracked. The frequent use of psychosocial exclusions is especially compromising to generalizability because chronic pain commonly co-occurs with psychiatric comorbidities. Inclusion of more representative patients in research samples can reduce recruitment barriers and broaden the generalizability of findings in patients with chronic pain. We also call for more studies that examine the use of exclusion criteria in chronic pain trials to better understand their implications.